The School of Al-Hanafiyia in Damascus during the ring of Sultan Noradin Mahmud son of Zanke )549- 569 HC1154 / 1173 –AD( - Mohammed, Shawkat A. (Humanities Journal of University of Zakho, 2018)
In the 6 HC/ 12 AD century, the city of Damascus was becoming so well-known especially during the reign of Sultan Nur al-Din Mahmud bin Zangi (549- 569 HC /1154 - 1173 AD), who took care of it greatly, what is more, it was a center of administration in the light of its geostrategic position of holy war against the crusaders, it should be putting out that it was certainly a connection bridge between Baghdad and Cairo, it was capable of political and military for uniting the Islamic groups and frontlines, it had played a crucial role of liberating Jerusalem from the crusaders. On other hand, Sultan Noureddine Mahmud, concentrated mostly on getting succeeded of his political necessity agendas to establish and strength the internal front of the Muslim world during his backing of the Sunni scholars to take over the schools, which had weaken Muslims and distinguishing them. Hence, his first preponderance and strengthening was contemplating on the religious sciences in his kingdom, during his era, Damascus was a center of developing intellectual and ideological, many Sunni scholars stayed in, furthermore, constructed a number of different Sunni school denominations. This study attempts to demonstrate the efforts of Sultan Noureddine Mahmud in this regard during his concentration on constructing Sunni schools in Damascus, specifically his contemplation on Hanafi school, as he believed in this kind of schools, respectively. This article is divided into three sections: First section endeavours to show general condition of Damascus during the period of Sultan Noradin Mahmud. Second section allocates to illustrate Sulatan’s supports to Sunni schools in general as well as Hanafi school in particular. Third section is being allocated to clarify the approaches of school of Hanafi in Damascus that it got, it programmer and those scholars who taught at this school.